Assessment of BMI in Medical students and its correlation with Blood pressure - Ahmed, Afsana; Ara, Shamim; Chowdhury, Achinto N; Rahman, Marufur; Malek, R; Rahman, Md Shamsur (Journal of Dhaka National Medical College & Hospital, 2013)
Overweight and obesity represent a rapidly growing threat to the world population and reached epidemic proportion in many Asian countries. These countries are facing grave burden of obesity related disorders like Hypertension, Diabetes mellitus, CVD which develop at a younger age than in western population. Concern grows that the current dramatic rise of obesity among adolescents portends a future wave of increasing cardiovascular disease. Body mass index has been identified by World Health Organization as most useful epidemiological measure of obesity. The present cross sectional study was conducted in the Department of Biochemistry in Dhaka National Medical College during the period from January 2012 to June 2012. A total of 205 medical students of 1st & 2 year, age ranging from 18 to 20 years were recruited in this study as study subjects. We observed frequency and distribution of overweight & obesity among medical students and found that a substantial proportion of medical students were overweight and obese. Among the total 205 study subjects, 130(63.41%) had normal BMI ranging from (18.5-24.9) kg /m2, 45(21.95%) were overweight, BMI ranging from (25-29:9) kg/m3 and 12(5.85%) were obese BMI >=30 kg/m2. The total number of underweight subjects was 45 that correspond to 21.95%. We also examined the relationship of BMI with systolic and diastolic blood pressure. The results of this study showed that BMI is positively correlated with Systolic blood pressure (p=0.039) & there was a linear relationship between BMI & diastolic blood pressure which was also statistically significant (p=0.005). The present findings emphasize the importance of the prevention of obesity in order to prevent future obesity related problems such as hypertension in adolescent. J. Dhaka National Med. Coll. Hos. 2013; 19 (01): 32-34